Teaching Pedagogical Approaches to Teaching the Pa'gellu' Dance to International Students in the BIPA Program - Reni Lolotandung; Trivena Trivena; Hakpantria Hakpantria; Tadius Tadius; Mersilina Luther Patintingan; Irnes Bulan Dari; Bhakti Sharma; Eliza Prall (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Indonesian Language for Foreign Speakers (BIPA) program at the Christian University of Indonesia Toraja (UKI Toraja) not only facilitates Indonesian language acquisition for international students but also introduces them to local culture. One key element of this cultural immersion is the Pa’gellu’ dance—a traditional performance of the Toraja people. This study employed a descriptive qualitative approach to examine the instructional strategies used in teaching the Pa’gellu’ dance to 17 international students from the University of Western Australia, Denpasar campus. Data were collected through structured observations, focusing on students’ engagement across seven instructional stages: Introduction and Theory, Basic Practice, Technique Refinement, Costume and Performance, Cultural Integration, Evaluation, and Staging. Findings reveal that international students successfully met the learning objectives. They demonstrated the ability to recognize, practice, and perform the Pa’gellu’ dance in a culminating presentation. Although the teaching structure mirrored that used for local students, the content was simplified for non-native participants. Instructional methods included lectures, demonstrations, guided practice, drills, simulations, and performance exercises. Despite linguistic and cultural barriers, students were able to grasp the core techniques of the Pa’gellu’ dance. The study suggests that immersive, performance-based pedagogy can effectively bridge cultural and linguistic gaps in arts education for foreign learners.